Manajemen Resiko Keamanan Aset Informasi Pada Puskesmas Pancur Batu Tuntungan - amri , hairul; awilo haryada, alwi; Aceh, Kairul Abdi; Ikhwan, Ali (Jurnal Sains dan Teknologi (JSIT), 2022)
Information security risk management is an important aspect of managing information systems at the Pancur Batu Health Center. This study aims to identify threats and risks that may occur to IT assets, as well as provide recommendations for appropriate risk management. The method used is ISO 27005/2011. The results of the study show that the overall security risk of IT assets is moderate and relatively small. The main recommendations given are the implementation of asset management policies and SOPs. Further research development will focus on assessing and managing existing threat risks to maintain good service.